2008
DOI: 10.1038/oby.2008.330
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure and Adiposity in Nigerian and African‐American Women

Abstract: Objective: Obesity is a prevalent condition in industrialized societies and is increasing around the world. We sought to assess the relative importance of resting energy expenditure (REE) and activity EE (AEE) in two populations with different rates of obesity. Methods and Procedures: Women of African descent between 18 and 59 years of age were recruited from rural Nigeria and from metropolitan Chicago. Total EE (TEE) was measured using the doubly labeled water (DLW) technique and REE by indirect calorimetry; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…However, research in humans and animal models indicate that physical activity is not necessarily related to obesity predisposition (12,13). In contrast to the common belief that physical activity is a key factor in obesity development in humans, studies have shown that energy expenditure in activity may play less of a role in the development of obesity than anticipated (31). Inactivity may be a consequence rather than a cause of obesity in children (32).…”
Section: Discussionmentioning
confidence: 82%
“…However, research in humans and animal models indicate that physical activity is not necessarily related to obesity predisposition (12,13). In contrast to the common belief that physical activity is a key factor in obesity development in humans, studies have shown that energy expenditure in activity may play less of a role in the development of obesity than anticipated (31). Inactivity may be a consequence rather than a cause of obesity in children (32).…”
Section: Discussionmentioning
confidence: 82%
“…These findings agree with those of Esliger et al (18), who reported high levels of PA in a sample of Amish children residing in Canada. The magnitude of the differences in PA between the OOA and the ES is intriguing because other studies (6,7) comparing groups whose environments were thought to differ crucially found that the groups had similar levels of PA. The exact origins of the differences between OOA and ES children are unclear, but certain circumstances deserve mention.…”
Section: Discussionmentioning
confidence: 94%
“…These voluntary constraints result in a lifestyle resembling that of farming Americans or Europeans a century or two ago. Although one might think that these circumstances promote greater levels of PA in OOA children compared with non-Amish children, the null hypothesis is favored by studies (6,7) finding similar PA levels in other groups whose environments differ greatly (e.g., individuals residing in the U.S. and Nigeria).…”
mentioning
confidence: 99%
“…Many experts argue that a decline in PA, particularly from occupation-related activities, is a key contributor to the current obesity epidemic (Archer et al, 2013; Blair, Archer & Hand, 2013; Hill & Peters, 2013; Popkin, 2001; Popkin, Adair & Ng, 2012; Popkin & Gordon-Larsen, 2004); however, prospective longitudinal studies employing objective measures of PA have not identified a meaningful relationship between weight gain and PA (Dugas et al, 2014; Ebersole et al, 2008; Luke et al, 2014; Swinburn, Sacks & Ravussin, 2009; Tataranni et al, 2003). The debate over the primary determinants of the worldwide obesity epidemic is more than simply academic; understanding obesity’s etiology is critical for informing policy and allocating scarce public health funding.…”
Section: Introductionmentioning
confidence: 99%